2016
DOI: 10.7863/ultra.15.05071
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Transvaginal Sonography and Magnetic Resonance Imaging for Local Staging of Cervical Cancer

Abstract: Three-dimensional sonography showed good agreement with MRI for assessing parametrial infiltration and bladder involvement in cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Recently, a study has been published on the correlation between the accuracy of 2D and 3D US and MRI on parametrial infiltration, showing a high correlation (79%), similar to our own results (84%) [15]. In another recent study, 3D sonography showed good agreement with MRI for assessing parametrial infiltration and bladder involvement [16]. These studies could not use histology as the gold standard to evaluate the real parametrial infiltration.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, a study has been published on the correlation between the accuracy of 2D and 3D US and MRI on parametrial infiltration, showing a high correlation (79%), similar to our own results (84%) [15]. In another recent study, 3D sonography showed good agreement with MRI for assessing parametrial infiltration and bladder involvement [16]. These studies could not use histology as the gold standard to evaluate the real parametrial infiltration.…”
Section: Discussionsupporting
confidence: 85%
“…31Y34 However, 2D TVUS and 3D TVUS were also shown to have good correlation with MRI in size estimation for cervical cancer. 35,36 The agreement between TVUS and pathological examination with regard to tumor size was also shown to be highly correlated, with a coefficient value of 0.92. 37 In a recent European multicenter trial along with high accurate preoperative assessment, it was emphasized that ultrasonography may be more accurate than MRI in detecting residual tumors and assessing parametrial invasion.…”
Section: Discussionmentioning
confidence: 80%
“…Some, comparing sonographic and MRI evaluation in assessing the presence and extent of disease, included both patients with early‐stage disease undergoing primary surgery and those with locally advanced cervical cancer undergoing neoadjuvant treatment. In all previous studies, the ultrasound scan was performed only before or only after treatment. In contrast, in the present study we analyzed ultrasound parameters only in patients undergoing neoadjuvant chemoradiation and we performed the examinations before, after and during treatment.…”
Section: Discussionmentioning
confidence: 99%